Feline dystocia and kitten mortality up to 12 weeks in pedigree cats - Černá, Petra; Pugalendhi, Sneha Joseph; Shaw, Darren J; Gunn-Moore, Danièlle A (Journal of feline medicine and surgery, 2024)
OBJECTIVES: The aim of the present study was to establish the incidence of dystocia in pedigree cat breeds and investigate mortality rates in kittens up to the age of 12 weeks. METHODS: A retrospective study was conducted that utilised convenience sampling. Registered cat breeders from 29 countries whose cats had given birth within a single year (2019) were asked to complete an online questionnaire. This study is the third in a series over 30 years that have assessed changes in birth-related statistics in cat breeds. RESULTS: Data were collected from 448 breeders on 853 litters, with 3560 live-born kittens from 45 pedigree breeds (as per the queens' breed). The incidence of dystocia that required veterinary intervention was 14.9% and varied by breed (range 0-22.2%). Caesarean section was required for 10.7% of litters, most commonly in Cornish Rex cats. Despite apparent breed variation, there was no statistically significant difference among breeds. Queens aged over 5 years and litters of more than six kittens were associated with a reduced risk of dystocia, whereas a longer gestation period increased the risk. Bengal cats had the highest cumulative kitten mortality up to the age of 12 weeks (23.4%). Significant breed differences (P <0.001) were noted, with Ragdoll and Norwegian Forest Cats having lower litter mortality compared with Bengal and British Shorthair/Longhair cats. CONCLUSIONS AND RELEVANCE: The incidence of dystocia in pedigree cats was higher than the historical values for non-pedigree and pedigree cats. The age of the queen, gestation length and litter size affected the incidence of dystocia. Kitten mortality was affected by the requirement for caesarean section, presence of birth defects and breed.
Keywords: dystokie; Cats; Animals, Newborn; pregnancy; Retrospective Studies; těhotenství; Incidence; birth defects; mužské pohlaví; rodokmen; Pedigree; incidence; novorozená zvířata; kočky; kittens; Cat Diseases; Breeders; ženské pohlaví; zvířata; retrospektivní studie; Pregnancy; nemoci koček; Dystocia; Female; Male; Animals